MOLECULAR PREDICTIVE BIOMARKERS FOR ORAL SQUAMOUS CELL CARCINOMA IN HUMANS IN IBADAN, NIGERIA (2021)
Squamous Cell Carcinoma is the most prevalent malignant tumour of the oral cavity in humans. Late hospital presentation and diagnosis often result in high mortality, recurrence and metastatic rates. Prognosis is poor with a low 5-year survival rate. There is a possibility that molecular events underlie the aetiology of oral squamous cell carcinoma (OSCC) and could prove useful in predicting OSCC-susceptible individuals, but this information is largely lacking in Nigerian cohorts. Thus, this study was designed to identify molecular predictive diagnostic biomarkers for OSCC from patients in Ibadan. Using a retrospective-prospective study design, a total of 100 (58 males, 42 females) histologically-classified OSCC cases were identified from 1527 tumour cases recorded at the University College Hospital, Ibadan, Nigeria, between January 2004 and December 2015. Patients’ demographic variables were extracted. Archived formalin-fixed, paraffin-embedded tissue samples were retrieved and processed immunohistochemically for Epithelial Membrane Antigen (EMA) and cytokeratin protein expression. The DNA from samples was also profiled for aberrant CpG island methylation and genotypes of rs7528484 polymorphism in RUNX3 gene by methylation-specific and restriction fragment length polymorphism-PCR, respectively. Data were analysed using descriptive statistics, while association between patients’ demographic variables, aberrant CpG island methylation and rs7528484 polymorphism in RUNX3 were assessed by Pearson’s χ2 test at P≤0.05, Monte-Carlo exact test and Odds Ratios (OR) at Confidence Interval (CI) of 95%, respectively. The prevalence of OSCC was 6.5%. The moderately differentiated class was the most prevalent (65.0%), with a general prevalence peak at the seventh decade age group and the palate being the most affected location. EMA was expressed by the well and moderately differentiated classes, while cytokeratin was expressed by the well, moderately and poorly differentiated classes. RUNX3 promoter hypermethylation was detected in 45.0% of OSCC, suggesting that aberrant CpG island promoter hypermethylation in RUNX3 was prevalent in the disease. The rs7528484 polymorphism in RUNX3 was also detected with a genotype distribution of 52.7% (39) homozygote normal (CC), 28.4% (21) heterozygote mutant (CT), 18.9% (14) homozygote mutant (TT), and a C>T allelic ratio of 0.67:0.33. There was significant association between aberrant CpG island promoter hypermethylation in RUNX3 and tumour location (P<0.05). Genotypes of rs7528484 polymorphism in RUNX3 and their alleles were significantly associated with both male and female gender (P<0.05) and histologic class (P<0.05). Mutant genotypes (CT) and (TT) showed odds of predicting OSCC (OR 0.28, 95% CI: 0.1889 - 0.3711) and (OR 0.18, 95% CI: 0.1118 - 0.2482), respectively. Mutant allele (T) showed odds of predicting OSCC (OR 0.66, 95% CI: 0.52 - 0.80). Aberrant CpG island promoter hypermethylation of RUNX3 in combination with tumour location and rs7528484 polymorphism in RUNX3 in combination with gender served as epigenetic and genetic predictors, respectively for oral squamous cell carcinoma, while epithelial membrane antigen expression pattern served as an immunohistochemical predictor for oral squamous cell carcinoma.